Intrauterine insemination at the present time - Celis López, Alfredo (2014)
Intrauterine insemination is the first treatment option in the infertile couple in patients with unexplained infertility, minimal and mild endometriosis, subfertility for cervical factor, or subfertility for mild male factor. But its effectiveness has been questioned for the low success rates and probable risks as multiple pregnancy and ovarian hyperestimulation syndrome. Nevertheless it continues being a widely used technique due to its simplicity and low cost, advantages over in vitro fertilization. IVF provides better success rates and the possibility of only one embryo transfer and subsequent transfer of frozen embryos, thus decreasing the risks despite being more expensive. This review tries to establish what is intrauterine insemination status at present, if it continues being in forcé and if it has a place in the infertile couple treatment or it will be withdrawal due to IVF.